Being and Becoming: The Transmission of Living Values Across Generations - Bhattarai, Tikaram (GS WOW: Wisdom of Worthy Research Journal, 2025)
This research investigates the diverse methods of intergenerational transmission of enduring values—peace, love, respect, and cooperation— within the socio-cultural framework of Nepal. Employing a qualitative auto-ethnographic methodology, the study examines the researcher's selfnarratives derived from familial and educational contexts. The analysis is conceptually grounded in Maslow’s Need Hierarchy Theory, Durkheim’s Social Integration Theory, Hybridization Theory, and construction– deconstruction frameworks. The results show that value transmission is a dynamic and non-linear process that is influenced by purposeful behaviors, narrative instruction, and everyday encounters. Families serve as fundamental environments for nurturing living values through rituals, moral instruction, and ethical mentorship, whereas schools function as institutional catalysts that enhance social cohesiveness and collective accountability. The study further illustrates that Nepal's living values are perpetually negotiated, hybridized, produced, and dismantled throughout generations. This continual process is shaped by personal action, intergenerational discussion, and institutional mediation, cultivating a collective moral consciousness despite the contradictions between tradition and modernity